Can a curse become a name of a gadget? - Pisowicz, Andrzej (Baltistica, 2017)
This article investigates the origin of the word šâmurti used in modern Persian. The author claims that it is a loanword from Armenian going back to an attributive construction that was used in a specific context.
Keywords: Modern Persian; Armenian; etymology; loanword